A new polymorphic Hemilophini Thomson, 1868 from the Tumuc Humac inselbergs, French Guiana (Coleoptera, Cerambycidae, Lamiinae) - Touroult, Julien; Dalens, Pierre-Henri (Zootaxa, 2015)
A new Zeale Pascoe, 1866, Zeale granvillei sp. nov., is described from open areas at Mitaraka Mounts, French Guiana. The key to the species of Zeale is updated and the different forms of the new species are illustrated. A list of the material from Muséum national d’Histoire naturelle (Paris) in this genus is provided. Some aspects of its behavior are given, including its possible host plant, Ichtyothere granvillei H. Robinson (Asteraceae).